Quality, quantity and recovery of DNA content from routine blood samples and genotyping success rate: comparison between phenol chloroform method (PCM) with a new kit-based DNA extraction method (KBM) - M. G., Gopisankar; A., Surendiran; M., Hemachandren; S., Rajan (International Journal of Basic & Clinical Pharmacology, 2018)
Background: DNA extraction has become a baseline method for molecular biology studies. There are a variety of methods available for this purpose. Newer kit-based methods (KBM) are easy and less time consuming than traditional chemical methods of extraction like phenol chloroform method (PCM). Though estimates of quality from different methods are available in labels, this study compared the practical outcomes regarding quantity, quality, DNA recovery rate and assessed the outcomes at two different time points. Methods: This study was done as a secondary analysis from an ongoing project. The quantity and quality of DNA isolated from the same group of 100 deidentified blood samples by PCM and KBM were analysed using Multi analyzer and repeated after a period of 3 months. Genotyping of the samples were done by RT-PCR. The quantity, quality and amplification proportion were compared between two groups to reach the inference. Results: The median (range) concentration of DNA by PCM was 543.27 (960.59) µg/ml and that of KBM was 32.115 (36.73) µg/ml. The quality of DNA as measured by absorbance at 260/280 nm was 1.84 in PCM and 1.81 in KBM (p>0.05). Genotyping success rate was 78% in PCM and 98% in KBM (p = 0.002). The DNA recovery rate was 96% in PCM and 80% in KBM (p=0.014). Conclusions: The median concentration of DNA obtained from PCM was more compared to KBM. The quality of DNA was comparable in both the groups. The genotyping success rate was more in KBM group. The DNA recovery rate at 3 months was more in PCM group.